If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(8 + -1k) = 98 (8 * 7 + -1k * 7) = 98 (56 + -7k) = 98 Solving 56 + -7k = 98 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Add '-56' to each side of the equation. 56 + -56 + -7k = 98 + -56 Combine like terms: 56 + -56 = 0 0 + -7k = 98 + -56 -7k = 98 + -56 Combine like terms: 98 + -56 = 42 -7k = 42 Divide each side by '-7'. k = -6 Simplifying k = -6
| 25+(30/2)-1 | | (x-2)(x-3)(4/(-x+2)(-x-3))=0 | | 2-3p=17 | | 9x+54=32 | | -2=(3-5x) | | ((10x-1)-(5x+1))=61 | | 25+30/(2-1) | | 3x/20+5x/7-1/14 | | 6(1-4b)=-114 | | -6x+10=153+7x | | 4y^4-101y^2+25=0 | | 19+(-2)= | | 25+(30/2-1) | | 4h+-1=4h+7 | | 2+4(4n-3)=-5(6n+8)-8n | | 2x-12+6=4x-2 | | 80-x=3(90-x)+10 | | -11=-4(4+2m) | | 30+5b=-5(b-4) | | -38-4a=2(5-5a) | | -31=9-6p-7p | | 3=-2*1+b | | 324=-6(7x-5) | | -8=6g+3 | | -2(x+3x)=4x-3 | | -11=-4(4+2) | | 23/6/38/6 | | h=-16t^2+100+30 | | (x+9)(x+5)=(x+1)(x+1) | | 6x+4x-2=-22 | | z^2/6-3z/2-27=0 | | 5x+-2=9x+4 |